2021
DOI: 10.5194/gmd-2021-332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementation and validation of a new irrigation scheme in the ISBA land surface model

Abstract: Abstract. With an increase in the number of natural processes represented, global land surface models (LSMs) have become more and more accurate in representing natural terrestrial ecosystems. However, they are still limited, especially in the representation of the impact of agriculture on land surface variables. This is particularly true for agro-hydrological processes related to a strong human control on freshwater. While most LSMs consider natural processes only, the development of human-related processes, e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The scale of the effort and investment given by national centres to develop and improve their land-surface modelling component is well illustrated by Boussetta et al (2021), with their description of ECLand, the land-surface modelling system at the European Centre for Medium-Range Weather Forecasts (ECMWF). Other recent studies to be noted include those of Druel et al (2021), Li et al (2021), and Takata and Hanasaki (2021).…”
Section: Introductionmentioning
confidence: 99%
“…The scale of the effort and investment given by national centres to develop and improve their land-surface modelling component is well illustrated by Boussetta et al (2021), with their description of ECLand, the land-surface modelling system at the European Centre for Medium-Range Weather Forecasts (ECMWF). Other recent studies to be noted include those of Druel et al (2021), Li et al (2021), and Takata and Hanasaki (2021).…”
Section: Introductionmentioning
confidence: 99%
“…The authors realized a study in India, where irrigation provides a large contribution to winter crop production, and they found that data assimilation (DA) of total water storage (TWS) RS observations into the catchment land surface model (CLSM) introduces a negative trend in groundwater due to pumping for irrigation, along with an associated erroneous negative trend in modelled evapotranspiration when irrigation is unmodelled. Other studies have attempted to incorporate irrigation schemes into global LSMs, including the Interaction between Soil, Biosphere, and Atmosphere (ISBA) LSM (Druel et al, 2021), the Community Land Model (CLM; Pokhrel et al, 2012), and the Organizing Carbon and Hydrology in Dynamic Ecosystems (ORCHIDEE) model (De Rosnay et al, 2003), demonstrating the regional impact of irrigation on different water storages and on energy partitioning between sensible and latent heat fluxes (Lawston et al, 2015). Different types of irrigation systems were also implemented into the NASA Land Information System (LIS; Kumar et al, 2006;Peters-Lidard et al, 2007) framework and coupled with several LSMs, such as the Noah LSM (Chen et al, 1996;Chen and Dudhia, 2001;Mahrt and Pan, 1984) and the Noah-MP LSM (Niu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The authors realized a study in India, where irrigation provides a large contribution to winter crop production, and they found that data assimilation (DA) of total water storage (TWS) RS observations into the Catchment land surface model (CLSM) introduces a negative trend in groundwater due to pumping for irrigation along with an associated erroneous negative trend in modelled evapotranspiration when irrigation is unmodelled. Other studies have attempted to incorporate irrigation schemes into global LSMs, including the Interaction between Soil, Biosphere, and Atmosphere (ISBA) LSM (Druel et al, 2021), the Community Land Model (CLM; Pokhrel et al, 2012) and the Organizing Carbon and Hydrology in Dynamic Ecosystems (ORCHIDEE) model (De Rosnay et al, 2003), demonstrating the regional impact of irrigation on different water storages and on energy partitioning between sensible and latent heat fluxes (Lawston et al, 2015). Different types of irrigation systems were also implemented into the NASA Land Information System (LIS) framework and coupled with several LSMs, such as the Noah LSM (Chen et al, 1996;Chen and Dudhia, 2001;Mahrt and Pan, 1984) and the Noah-MP LSM (Niu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%